Developing Artificial Intelligence Sustainably : Toward a Practical Code of Conduct for Disruptive Technologies - Myers, Gordon; Nejkov, Kiril (International Finance Corporation, Washington, DC, 2020)
The adoption and diffusion of artificial intelligence and other disruptive technologies will play an important role in market creation and growth. Development finance institutions have a role to play in leveraging their investments to ensure that these technologies sustain both growth and development objectives. To this end, the authors propose adoption of a Technology Code of Conduct as a framework, supported by a set of practical tools for its operationalization, to assist IFC’s clients engaged in technology intensive project.